Wall cloth for purifying formaldehyde and preparation method thereof
By using composite nanofiber membranes and phosphorus-nitrogen flame retardant fiber fabrics in wall cloth, combined with modified carbon nitride and phosphorus-nitrogen flame retardant, the problem of degradation of formaldehyde purification effect during long-term use of wall cloth is solved, and the problem of degradation of formaldehyde purification effect during long-term use is achieved. Efficient formaldehyde removal and flame retardant properties ensure the safety of the indoor environment.
Patent Information
- Application Number
- CN202411055067.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2024-12-17
AI Technical Summary
The existing wall cloth is saturated during long-term use, resulting in a decrease in the formaldehyde purification effect and is unable to effectively retardant flame.
The composite nanofiber membrane and phosphorus-nitrogen flame retardant fiber fabric are used to improve the photocatalytic performance and flame retardant properties through the synergistic effect of modified carbon nitride and phosphorus-nitrogen flame retardant, and a wall cloth for purifying formaldehyde is prepared.
It significantly improves the formaldehyde removal rate and flame retardant properties of the wall cloth, extends the adsorption capacity, and ensures the purification effect and safety during long-term use.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of home decoration, in particular to a wall cloth for purifying formaldehyde and a preparation method thereof. Background Art
[0002] As living standards improve, people's requirements for the comfort and safety of their living environment are also increasing. Formaldehyde, as a common indoor air pollutant, mainly comes from decoration materials, furniture, etc. Long-term exposure to high-concentration formaldehyde environments may have adverse effects on human health, such as irritation to the eyes, nose and throat, and may even cause more serious health problems.
[0003] In order to meet consumers' demand for a healthier indoor environment, the wall cloth industry has begun to actively explore wall cloth products with the function of purifying formaldehyde. These wall cloths have the ability to adsorb and decompose formaldehyde by adding specific formaldehyde-removing molecules or technologies during the production process, such as photocatalyst technology, activated carbon adsorption, etc. However, the purification effect is limited. During long-term use, the adsorption sites on the surface of the wall cloth will gradually become saturated, resulting in a decrease in its adsorption capacity. Therefore, it is particularly important to invent a wall cloth that can purify formaldehyde and is flame-retardant. Summary of the invention
[0004] The purpose of the present invention is to provide a wall cloth for purifying formaldehyde and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a wall cloth for purifying formaldehyde, wherein the wall cloth for purifying formaldehyde comprises a composite nanofiber membrane and a phosphorus-nitrogen flame-retardant fiber fabric.
[0006] Furthermore, the composite nanofiber is made from modified carbon nitride and polyvinyl alcohol 1799.
[0007] Furthermore, the phosphorus-nitrogen flame-retardant fiber fabric is prepared by pretreating cotton fiber with tris(hydroxymethyl)aminomethane, dicyandiamide, phosphorus pentoxide, urea and alkali.
[0008] Furthermore, the modified carbon nitride is prepared from thiourea, titanium carbide and triphenylphosphine.
[0009] Furthermore, a method for preparing a wall cloth for purifying formaldehyde comprises the following preparation steps:
[0010] (1) Thiourea, titanium carbide, triphenylphosphine and deionized water are mixed in a mass ratio of 2:2:0.002-0.01:6, ultrasonicated for 15-30 minutes, stirred at room temperature and 30-50 rpm for 15-30 minutes, heated to 60-70°C and dried for 3 hours, taken out, ground into powder, calcined at a heating rate of 2°C / min from room temperature to 550°C for 3 hours, washed with deionized water 3 times, heated to 60°C and dried for 12 hours to obtain modified carbon nitride; polyvinyl alcohol 1799 and deionized water are mixed in a mass ratio of 1:9, modified carbon nitride of 0.001-0.005 times the mass of polyvinyl alcohol 1799 is added, stirred at 1000-1200 rpm for 1 hour to obtain a spinning solution, and centrifugal electrospinning is performed to obtain a composite nanofiber membrane;
[0011] (2) dicyandiamide and deionized water are uniformly mixed in a mass ratio of 9 to 12:250 to obtain solution A, tris(hydroxymethyl)aminomethane and deionized water are uniformly mixed in a mass ratio of 12 to 14:250 to obtain solution B, solution A is heated to 65 to 70°C, solution B is added in an amount 1 times the volume of solution A to obtain a mixed solution, the solution is heated to 65°C and stirred at 50 to 80 rpm for 3 to 4 hours, phosphorus pentoxide is added in an amount 1 to 2 times the mass of tris(hydroxymethyl)aminomethane, the temperature is raised to 80 to 90°C and reacted for 2 to 3 hours, urea is added in an amount 2 to 3 times the mass of tris(hydroxymethyl)aminomethane, the temperature is raised to 130 to 150°C and reacted for 1 hour, the solution is cooled to room temperature, the solution is heated to 60 to 80°C and dried for 1 to 2 hours, the solution is washed with anhydrous ethanol for 3 times, the solution is heated to 60°C and dried for 20 to 30 minutes to obtain a phosphorus-nitrogen flame retardant;
[0012] (3) mixing a phosphorus-nitrogen flame retardant, dicyandiamide and deionized water in a mass ratio of 1.5 to 2:1:20 to obtain a flame retardant solution, and then soaking the alkali pretreated cotton fiber to obtain a phosphorus-nitrogen flame retardant fiber, and then weaving it to obtain a phosphorus-nitrogen flame retardant fiber fabric with a gram weight of 100 to 150 g / m2;
[0013] (4) Measure the size of the wall, cut the composite nanofiber membrane and phosphorus nitrogen flame retardant fiber fabric into the required shape and size, cut the hot melt adhesive into small pieces, place them between the composite nanofiber membrane and the phosphorus nitrogen flame retardant fiber fabric and align them, heat the iron to 80-140°C, and move it slowly on the fabric until the hot melt adhesive is completely bonded, thereby obtaining a formaldehyde-purifying wall cloth.
[0014] Furthermore, the specific parameters of the centrifugal electrospinning in the above step (1) are: the spinning machine voltage is set to 10 kV, the distance between the receiving plate and the spinning head is 10 cm, the rotation speed is 3500 r / min, and the spinning time is 1 h.
[0015] Furthermore, the preparation method of the alkali pretreated cotton fiber in the above step (3) is: ultrasonically treat the cotton fiber with deionized water for 60 to 80 minutes, put it in an oven at 100 to 110° C. and dry it for 1 to 2 hours, add a 5% sodium hydroxide aqueous solution with a mass concentration of 1 to 2 times the mass of the cotton fiber, ultrasonically treat it for 50 to 60 minutes, wash it with deionized water until the pH value of the washing water is 7, heat it to 100° C. and dry it for 1 to 2 hours to obtain the alkali pretreated cotton fiber.
[0016] Furthermore, the specific process of the soaking treatment in the above step (3) is: immersing the alkali pretreated cotton fiber in the flame retardant solution at a bath ratio of 1:4-8, reacting for 60 seconds, rolling once, pre-baking at 90°C for 3 minutes, and baking at 150°C for 3 minutes.
[0017] Furthermore, the specific process of weaving the fabric in the above step (3) is: the warp yarn and the weft yarn are interlaced and woven, each warp yarn and the weft yarn pass through one, and then alternately interweave up and down to obtain the phosphorus-nitrogen flame-retardant fiber fabric.
[0018] Furthermore, in the above step (4), the hot melt adhesive is a modified polyurethane of a moisture-heat curing reaction type, and the total amount of the hot melt adhesive is 20 to 30 g / m 2 .
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The wall cloth for purifying formaldehyde prepared by the invention comprises a composite nanofiber membrane and a phosphorus-nitrogen flame-retardant fiber fabric, and has the effects of purifying formaldehyde and flame retardancy.
[0021] Firstly, the present invention calcines thiourea, titanium carbide and triphenylphosphine to obtain a modified carbon nitride composite material, and the charge transfer is transferred from the 2D carbon nitride conduction band to the 0D titanium dioxide conduction band, and the generated titanium dioxide quantum dots can play the role of electron acceptor, enhance the ability to capture transition electrons, and improve the spectral response width and photocatalytic performance; the introduction of triphenylphosphine retains the crystal structure of carbon nitride, adjusts the molecular structure, makes the material looser, and synergistically improves the photocatalytic performance of carbon nitride with titanium dioxide quantum dots; under the excitation of visible light, strong redox free radicals are generated to oxidize the carbon-hydrogen bonds in formaldehyde, and effectively decompose the formaldehyde into harmless substances;
[0022] Secondly, the present invention mixes tris(hydroxymethyl)aminomethane and dicyandiamide, adds the amino group of tris(hydroxymethyl)aminomethane and the carbon-nitrogen triple bond of dicyandiamide to generate a biguanide structure, adds phosphorus pentoxide to esterify, adds urea, and prepares a phosphorus-nitrogen flame retardant through acid-base neutralization; soaks the fiber in a flame retardant solution, uses dicyandiamide as a catalyst, and makes the flame retardant covalently bonded to the fiber molecules, which is not easy to fall off; the flame retardant decomposes into phosphoric acid at high temperature, which can accelerate the speed of dehydration of the fiber surface into carbon, quickly generates a dense carbon layer, and effectively isolates the fire source and combustibles. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the wall cloth for purifying formaldehyde prepared in the following examples are as follows:
[0025] Flame retardancy: The limiting oxygen index of the embodiments and comparative examples was determined according to GB / T 2406-93. A group of samples were tested in different oxygen concentrations. The minimum oxygen concentration at which the sample just maintained stable combustion was measured, expressed as the volume percentage of the oxygen content in the mixed gas.
[0026] Formaldehyde concentration test: The formaldehyde concentration was tested using the formaldehyde detector method. The formaldehyde content detector was the A25F air quality detector with a range of 0 to 2 mg / m 3 , resolution is 0.01mg / m 3 Formaldehyde removal rate = (initial concentration - final concentration) / initial concentration × 100%
[0027] Example 1
[0028] (1) Thiourea, titanium carbide, triphenylphosphine and deionized water were mixed in a mass ratio of 2:2:0.004:6, ultrasonicated for 15 min, stirred at room temperature and 30 rpm for 15 min, heated to 60 ° C and dried for 3 h, taken out, ground into powder, calcined at a heating rate of 2 ° C / min from room temperature to 550 ° C for 3 h, washed with deionized water 3 times, heated to 60 ° C and dried for 12 h to obtain modified carbon nitride; polyvinyl alcohol 1799 and deionized water were mixed in a mass ratio of 1:9, modified carbon nitride with a mass of 0.001 times of polyvinyl alcohol 1799 was added, stirred at 1000 rpm for 1 h to obtain spinning solution, the spinning machine voltage was set to 10 kV, the distance between the receiving plate and the spinning head was 10 cm, the rotation speed was 3500 r / min, the spinning time was 1 h, and centrifugal electrospinning was performed to obtain a composite nanofiber membrane;
[0029] (2) dicyandiamide and deionized water are uniformly mixed in a mass ratio of 9:250 to obtain solution A, tris(hydroxymethylaminomethane) and deionized water are uniformly mixed in a mass ratio of 12:250 to obtain solution B, solution A is heated to 65°C, solution B is added in an amount 1 times the volume of solution A to obtain a mixed solution, the solution is heated to 65°C and stirred at 50 rpm for 3 hours, phosphorus pentoxide is added in an amount 1 times the mass of tris(hydroxymethylaminomethane), the temperature is raised to 80°C and reacted for 2 hours, urea is added in an amount 2 times the mass of tris(hydroxymethylaminomethane), the temperature is raised to 130°C and reacted for 1 hour, the solution is cooled to room temperature, the solution is heated to 60°C and dried for 1 hour, the solution is washed 3 times with anhydrous ethanol, and the solution is heated to 60°C and dried for 20 minutes to obtain a phosphorus-nitrogen flame retardant;
[0030] (3) The cotton fiber was ultrasonically treated with deionized water for 60 minutes, placed in an oven and dried at 100°C for 1 hour, a 5% sodium hydroxide aqueous solution with a mass concentration of 1 times the mass of the cotton fiber was added, ultrasonicated for 50 minutes, washed with deionized water until the pH value of the washing water was 7, heated to 100°C and dried for 1 hour to obtain alkali-pretreated cotton fiber; phosphorus-nitrogen flame retardant, dicyandiamide and deionized water were mixed at a mass ratio of 1.5:1:20 to obtain a flame retardant solution, and then the alkali-pretreated cotton fiber was completely immersed in the flame retardant solution at a bath ratio of 1:4, reacted for 60 seconds, rolled once, pre-baked at 90°C for 3 minutes, and baked at 150°C for 3 minutes. The phosphorus-nitrogen flame retardant fiber was obtained, and then the warp and weft yarns were interlaced and woven, each warp and weft yarn passed through one, and then alternately interlaced up and down to obtain a gram weight of 100g / m 2 Phosphorus and nitrogen flame retardant fiber fabrics;
[0031] (4) Measure the wall size, cut the composite nanofiber membrane and phosphorus nitrogen flame retardant fiber fabric into the required shape and size, cut the hot melt adhesive into small pieces, place them between the composite nanofiber membrane and phosphorus nitrogen flame retardant fiber fabric and align them. The total amount is 20g / m 2 , heat the iron to 100℃ and move it slowly on the fabric until the hot melt adhesive is completely bonded to obtain formaldehyde-purified wall covering.
[0032] Example 2
[0033] (1) Thiourea, titanium carbide, triphenylphosphine and deionized water were mixed in a mass ratio of 2:2:0.006:6, ultrasonicated for 20 min, stirred at room temperature and 40 rpm for 20 min, heated to 65 ° C and dried for 3 h, taken out, ground into powder, calcined at a heating rate of 2 ° C / min from room temperature to 550 ° C for 3 h, washed with deionized water 3 times, heated to 60 ° C and dried for 12 h to obtain modified carbon nitride; polyvinyl alcohol 1799 and deionized water were mixed in a mass ratio of 1:9, 0.003 times the mass of polyvinyl alcohol 1799 was added to the modified carbon nitride, stirred at 1100 rpm for 1 h to obtain a spinning solution, the spinning machine voltage was set to 10 kV, the distance between the receiving plate and the spinning head was 10 cm, the rotation speed was 3500 r / min, the spinning time was 1 h, and centrifugal electrospinning was performed to obtain a composite nanofiber membrane;
[0034] (2) dicyandiamide and deionized water are uniformly mixed at a mass ratio of 10:250 to obtain solution A, tris(hydroxymethyl)aminomethane and deionized water are uniformly mixed at a mass ratio of 13:250 to obtain solution B, solution A is heated to 70°C, solution B is added in an amount 1 times the volume of solution A to obtain a mixed solution, the solution is heated to 65°C and stirred at 70 rpm for 4 hours, phosphorus pentoxide is added in an amount 1.5 times the mass of tris(hydroxymethyl)aminomethane, the temperature is raised to 85°C and reacted for 3 hours, urea is added in an amount 2.5 times the mass of tris(hydroxymethyl)aminomethane, the temperature is raised to 140°C and reacted for 1 hour, the solution is cooled to room temperature, the solution is heated to 70°C and dried for 2 hours, the solution is washed with anhydrous ethanol for 3 times, and the solution is heated to 60°C and dried for 30 minutes to obtain a phosphorus-nitrogen flame retardant;
[0035] (3) The cotton fiber was ultrasonically treated with deionized water for 70 minutes, placed in an oven and dried at 110°C for 2 hours, and a 5% sodium hydroxide aqueous solution with a mass concentration of 1.5 times the mass of the cotton fiber was added, ultrasonicated for 55 minutes, washed with deionized water until the pH value of the washing water was 7, heated to 100°C and dried for 2 hours to obtain alkali-pretreated cotton fiber; phosphorus-nitrogen flame retardant, dicyandiamide and deionized water were mixed at a mass ratio of 1.8:1:20 to obtain a flame retardant solution, and then the alkali-pretreated cotton fiber was completely immersed in the flame retardant solution at a bath ratio of 1:6, reacted for 60 seconds, rolled once, pre-baked at 90°C for 3 minutes, and baked at 150°C for 3 minutes. The phosphorus-nitrogen flame retardant fiber was obtained, and then the warp and weft yarns were interlaced and woven, and each warp and weft yarn passed through one, and then alternately interlaced up and down to obtain a gram weight of 130g / m 2 Phosphorus and nitrogen flame retardant fiber fabrics;
[0036] (4) Measure the wall size, cut the composite nanofiber membrane and phosphorus nitrogen flame retardant fiber fabric into the required shape and size, cut the hot melt adhesive into small pieces, place them between the composite nanofiber membrane and phosphorus nitrogen flame retardant fiber fabric and align them. The total amount is 25g / m 2 , heat the iron to 120℃ and move it slowly on the fabric until the hot melt adhesive is completely bonded to obtain formaldehyde-purified wall covering.
[0037] Example 3
[0038] (1) Thiourea, titanium carbide, triphenylphosphine and deionized water were mixed in a mass ratio of 2:2:0.01:6, ultrasonicated for 30 minutes, stirred at room temperature and 50 rpm for 30 minutes, heated to 70°C and dried for 3 hours, taken out, ground into powder, calcined at a heating rate of 2°C / min from room temperature to 550°C for 3 hours, washed with deionized water 3 times, heated to 60°C and dried for 12 hours to obtain modified carbon nitride; polyvinyl alcohol 1799 and deionized water were mixed in a mass ratio of 1:9, modified carbon nitride with a mass of 0.005 times of polyvinyl alcohol 1799 was added, stirred at 1200 rpm for 1 hour to obtain spinning solution, the spinning machine voltage was set to 10 kV, the distance between the receiving plate and the spinning head was 10 cm, the rotation speed was 3500 r / min, the spinning time was 1 hour, and centrifugal electrospinning was performed to obtain a composite nanofiber membrane;
[0039] (2) dicyandiamide and deionized water are uniformly mixed in a mass ratio of 12:250 to obtain solution A, tris(hydroxymethyl)aminomethane and deionized water are uniformly mixed in a mass ratio of 14:250 to obtain solution B, solution A is heated to 70°C, solution B is added in an amount 1 times the volume of solution A to obtain a mixed solution, the solution is heated to 65°C and stirred at 80 rpm for 4 hours, phosphorus pentoxide is added in an amount 2 times the mass of tris(hydroxymethyl)aminomethane, the temperature is raised to 90°C and reacted for 3 hours, urea is added in an amount 3 times the mass of tris(hydroxymethyl)aminomethane, the temperature is raised to 150°C and reacted for 1 hour, the solution is cooled to room temperature, the solution is heated to 80°C and dried for 2 hours, the solution is washed with anhydrous ethanol for 3 times, and the solution is heated to 60°C and dried for 30 minutes to obtain a phosphorus-nitrogen flame retardant;
[0040] (3) The cotton fiber was ultrasonically treated with deionized water for 80 minutes, placed in an oven and dried at 110°C for 2 hours, a 5% sodium hydroxide aqueous solution with a mass concentration twice that of the cotton fiber was added, ultrasonicated for 60 minutes, washed with deionized water until the pH value of the washing water was 7, heated to 100°C and dried for 2 hours to obtain alkali-pretreated cotton fiber; phosphorus-nitrogen flame retardant, dicyandiamide and deionized water were mixed in a mass ratio of 2:1:20 to obtain a flame retardant solution, and then the alkali-pretreated cotton fiber was completely immersed in the flame retardant solution in a bath ratio of 1:8, reacted for 60 seconds, rolled once, pre-baked at 90°C for 3 minutes, and baked at 150°C for 3 minutes. The phosphorus-nitrogen flame retardant fiber was obtained; then the warp and weft yarns were interlaced and woven, each warp and weft yarn passed through one, and then alternately interlaced up and down to obtain a gram weight of 150g / m 2 Phosphorus and nitrogen flame retardant fiber fabrics;
[0041] (4) Measure the wall size, cut the composite nanofiber membrane and phosphorus nitrogen flame retardant fiber fabric into the required shape and size, cut the hot melt adhesive into small pieces, place them between the composite nanofiber membrane and phosphorus nitrogen flame retardant fiber fabric and align them. The total amount is 30g / m 2, heat the iron to 140℃ and move it slowly on the fabric until the hot melt adhesive is completely bonded to obtain formaldehyde-purified wall covering.
[0042] Comparative Example 1
[0043] The difference between Comparative Example 1 and Example 3 is only that step (1) is different. Step (1) is changed to: thiourea, titanium carbide and deionized water are mixed in a mass ratio of 2:2:6, ultrasonicated for 30 minutes, stirred at room temperature and 50 rpm for 30 minutes, heated to 70°C and dried for 3 hours, taken out, ground into powder, calcined from room temperature to 550°C at a heating rate of 2°C / min for 3 hours, washed with deionized water 3 times, heated to 60°C and dried for 12 hours to obtain modified carbon nitride; polyvinyl alcohol 1799 and deionized water are mixed in a mass ratio of 1:9, modified carbon nitride with a mass of 0.005 times that of polyvinyl alcohol 1799 is added, stirred at 1200 rpm for 1 hour to obtain a spinning solution, the spinning machine voltage is set to 10 kV, the distance between the receiving plate and the spinning head is 10 cm, the rotation speed is 3500 r / min, the spinning time is 1 hour, and centrifugal electrospinning is performed to obtain a composite nanofiber membrane.
[0044] Comparative Example 2
[0045] The difference between Comparative Example 2 and Example 3 is only the difference in step (2). Step (2) is changed to: dicyandiamide and deionized water are uniformly mixed in a mass ratio of 12:250 to obtain solution A, tris(hydroxymethyl)aminomethane and deionized water are uniformly mixed in a mass ratio of 14:250 to obtain solution B, solution A is heated to 70°C, solution B with a volume of 1 times that of solution A is added to obtain a mixed solution, the solution is heated to 65°C and stirred at 80 rpm for 4 h, urea with a mass of 3 times that of tris(hydroxymethyl)aminomethane is added, the temperature is raised to 150°C, the reaction is carried out for 1 h, the mixture is cooled to room temperature, heated to 80°C and dried for 2 h, washed with anhydrous ethanol 3 times, and heated to 60°C and dried for 30 min to obtain a phosphorus-nitrogen flame retardant.
[0046] Comparative Example 3
[0047] The difference between Comparative Example 3 and Example 3 is only the difference in step (2). Step (2) is changed to: dicyandiamide and deionized water are uniformly mixed in a mass ratio of 12:250 to obtain solution A, tris(hydroxymethyl)aminomethane and deionized water are uniformly mixed in a mass ratio of 14:250 to obtain solution B, solution A is heated to 70°C, solution B with a volume of 1 times that of solution A is added to obtain a mixed solution, the solution is heated to 65°C and stirred at 80 rpm for 4 h, phosphorus pentoxide with a mass of 2 times that of tris(hydroxymethyl)aminomethane is added, the temperature is raised to 90°C for reaction for 3 h, the solution is cooled to room temperature, the solution is heated to 80°C for drying for 2 h, the solution is washed 3 times with anhydrous ethanol, and the solution is heated to 60°C for drying for 30 min to obtain a phosphorus-nitrogen flame retardant.
[0048] Comparative Example 4
[0049] The difference between Comparative Example 4 and Example 3 is only the difference in step (3). Step (3) is changed to: ultrasonically treat the cotton fiber with deionized water for 80 minutes, put it in an oven at 110°C and dry it for 2 hours, add a 5% sodium hydroxide aqueous solution with a mass concentration twice the mass of the cotton fiber, ultrasonicate for 60 minutes, wash it with deionized water until the pH value of the washing water is 7, heat it to 100°C and dry it for 2 hours, and prepare alkali-pretreated cotton fiber; mix the phosphorus-nitrogen flame retardant and deionized water in a mass ratio of 2:20 to obtain a flame retardant solution, and then completely immerse the alkali-pretreated cotton fiber in the flame retardant solution in a bath ratio of 1:8, react for 60 seconds, roll it once, pre-bake it at 90°C for 3 minutes, and bake it at 150°C for 3 minutes. Prepare phosphorus-nitrogen flame-retardant fiber; then interweave the warp and weft yarns, each warp and weft yarn passes through one, and then alternately interweave up and down to obtain a gram weight of 150g / m 2 Phosphorus and nitrogen flame retardant fiber fabric.
[0050] Comparative Example 5
[0051] The difference between Comparative Example 5 and Example 3 is only the difference in step (3), and step (3) is changed to: phosphorus nitrogen flame retardant, dicyandiamide and deionized water are mixed in a mass ratio of 2:1:20 to obtain a flame retardant solution, and then the cotton fiber is completely immersed in the flame retardant solution at a bath ratio of 1:8, and after reacting for 60 seconds, it is rolled once, pre-baked at 90°C for 3 minutes, and baked at 150°C for 3 minutes. The phosphorus nitrogen flame retardant fiber is obtained; then the warp and weft yarns are interlaced and woven, each warp and weft yarn passes through one, and then alternately interlaced up and down, and the gram weight is 150g / m 2 Phosphorus and nitrogen flame retardant fiber fabric.
[0052] Effect example
[0053] Table 1 below shows the performance analysis results of the formaldehyde-purifying wall coverings of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0054] Table 1
[0055] Formaldehyde removal rate (%) Limiting oxygen index LOI (%) Example 1 74.33 47 Example 2 72.15 46 Example 3 77.27 48 Comparative Example 1 50.14 38.5 Comparative Example 2 44.58 34.1 Comparative Example 3 56.75 41 Comparative Example 4 60.18 38.7 Comparative Example 5 58.69 34.4
[0056] By comparing the experimental data of formaldehyde removal rate of the embodiment and the comparative example in Table 1, it can be found that thiourea, titanium carbide and triphenylphosphine are prepared by a one-step calcination method to modify the carbon nitride composite material, and the charge transfer is transferred from the 2D carbon nitride conduction band to the 0D titanium dioxide conduction band. The generated titanium dioxide quantum dots can act as electron acceptors, enhance the ability to capture transition electrons, enable electrons to quickly participate in the photocatalytic reaction, and improve the spectral response width and photocatalytic performance; the introduction of triphenylphosphine retains the crystal structure of carbon nitride, adjusts the molecular structure, makes the material looser, and synergizes with the titanium dioxide quantum dots to improve the nitrogen The flame retardant has the photocatalytic property of carbonization; under the excitation of visible light, it generates free radicals with strong redox property, oxidizes the carbon-hydrogen bonds in formaldehyde, and effectively decomposes formaldehyde into harmless substances; from the comparison of the limiting oxygen index (LOI) experimental data of the embodiment and the comparative example, it can be found that the flame retardant decomposes into phosphoric acid and nitrogen at high temperature, phosphoric acid can accelerate the speed of dehydration to carbonization on the fiber surface, quickly generate a dense carbon layer, isolate heat and oxygen from the outside, effectively isolate the fire source and combustibles, and play a role in the condensed phase flame retardant direction; nitrogen can dilute the oxygen concentration in the combustion range and the concentration of nearby combustible gases, and play a role in the gas phase flame retardant direction.
[0057] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A wall covering for purifying formaldehyde, characterized in that: The formaldehyde-purifying wall cloth comprises a composite nanofiber membrane and a phosphorus-nitrogen flame-retardant fiber fabric.
2. A wall covering for purifying formaldehyde according to claim 1, characterized in that: The composite nanofiber membrane is made of modified carbon nitride and polyvinyl alcohol 1799.
3. A wall covering for purifying formaldehyde according to claim 1, characterized in that: The phosphorus-nitrogen flame-retardant fiber fabric is prepared by pretreating cotton fiber with tris(hydroxymethyl)aminomethane, dicyandiamide, phosphorus pentoxide, urea and alkali.
4. A wall covering for purifying formaldehyde according to claim 2, characterized in that: The modified carbon nitride is prepared from thiourea, titanium carbide and triphenylphosphine.
5. A method for preparing a wall cloth for purifying formaldehyde, characterized in that: The method comprises the following preparation steps: (1) Thiourea, titanium carbide, triphenylphosphine and deionized water are mixed in a mass ratio of 2:2:0.002-0.01:6, ultrasonicated for 15-30 minutes, stirred at room temperature and 30-50 rpm for 15-30 minutes, heated to 60-70°C and dried for 3 hours, taken out, ground into powder, calcined at a heating rate of 2°C / min from room temperature to 550°C for 3 hours, washed with deionized water 3 times, heated to 60°C and dried for 12 hours to obtain modified carbon nitride; polyvinyl alcohol 1799 and deionized water are mixed in a mass ratio of 1:9, modified carbon nitride of 0.001-0.005 times the mass of polyvinyl alcohol 1799 is added, stirred at 1000-1200 rpm for 1 hour to obtain a spinning solution, and centrifugal electrospinning is performed to obtain a composite nanofiber membrane; (2) dicyandiamide and deionized water are uniformly mixed in a mass ratio of 9 to 12:250 to obtain solution A, tris(hydroxymethyl)aminomethane and deionized water are uniformly mixed in a mass ratio of 12 to 14:250 to obtain solution B, solution A is heated to 65 to 70°C, solution B is added in an amount 1 times the volume of solution A to obtain a mixed solution, the solution is heated to 65°C and stirred at 50 to 80 rpm for 3 to 4 hours, phosphorus pentoxide is added in an amount 1 to 2 times the mass of tris(hydroxymethyl)aminomethane, the temperature is raised to 80 to 90°C and reacted for 2 to 3 hours, urea is added in an amount 2 to 3 times the mass of tris(hydroxymethyl)aminomethane, the temperature is raised to 130 to 150°C and reacted for 1 hour, the solution is cooled to room temperature, the solution is heated to 60 to 80°C and dried for 1 to 2 hours, the solution is washed with anhydrous ethanol for 3 times, the solution is heated to 60°C and dried for 20 to 30 minutes to obtain a phosphorus-nitrogen flame retardant; (3) A phosphorus-nitrogen flame retardant, dicyandiamide and deionized water are mixed in a mass ratio of 1.5 to 2:1:20 to obtain a flame retardant solution, and then the alkali pretreated cotton fiber is soaked to obtain a phosphorus-nitrogen flame retardant fiber, which is then woven to obtain a gram weight of 100 to 150 g / m 2 Phosphorus and nitrogen flame retardant fiber fabrics; (4) Measure the size of the wall, cut the composite nanofiber membrane and phosphorus nitrogen flame retardant fiber fabric into the required shape and size, cut the hot melt adhesive into small pieces, place them between the composite nanofiber membrane and the phosphorus nitrogen flame retardant fiber fabric and align them, heat the iron to 80-140°C, and move it slowly on the fabric until the hot melt adhesive is completely bonded, thereby obtaining a formaldehyde-purifying wall cloth.
6. The method for preparing a wall cloth for purifying formaldehyde according to claim 5, characterized in that: The specific parameters of the centrifugal electrospinning in the above step (1) are: the spinning machine voltage is set to 10 kV, the distance between the receiving plate and the spinning head is 10 cm, the rotation speed is 3500 r / min, and the spinning time is 1 h.
7. The method for preparing a wall cloth for purifying formaldehyde according to claim 5, characterized in that: The preparation method of the alkali pretreated cotton fiber in the above step (3) is: ultrasonically treat the cotton fiber with deionized water for 60 to 80 minutes, put it in an oven at 100 to 110° C. and dry it for 1 to 2 hours, add a 5% sodium hydroxide aqueous solution with a mass concentration of 1 to 2 times the mass of the cotton fiber, ultrasonically treat it for 50 to 60 minutes, wash it with deionized water until the pH value of the washing water is 7, heat it to 100° C. and dry it for 1 to 2 hours to obtain the alkali pretreated cotton fiber.
8. The method for preparing a wall cloth for purifying formaldehyde according to claim 5, characterized in that: The specific process of the soaking treatment in the above step (3) is: immersing the alkali pretreated cotton fiber in the flame retardant solution at a bath ratio of 1:4-8, reacting for 60 seconds, rolling once, pre-baking at 90°C for 3 minutes, and baking at 150°C for 3 minutes.
9. The method for preparing a wall cloth for purifying formaldehyde according to claim 5, characterized in that: The specific process of weaving the fabric in the above step (3) is as follows: the warp yarn and the weft yarn are interlaced and woven, each warp yarn and the weft yarn are passed through one, and then alternately interwoven up and down, and the gram weight is 100-150g / m 2 Phosphorus and nitrogen flame retardant fiber fabric.
10. The method for preparing a wall cloth for purifying formaldehyde according to claim 5, characterized in that: The hot melt adhesive in step (4) is a modified polyurethane of a moisture-heat curing reaction type, and the total amount of the hot melt adhesive is 20 to 30 g / m 2 .
Citation Information
Patent Citations
Formaldehyde-removal with visible light and antibacterial multifunctional air cleanser and preparation method thereof
CN108926994A
Nitrogen-phosphorus synergistic flame retardant modified cellulose film material and preparation method thereof
CN112521662A
Carbon nitride-polyvinyl alcohol composite antibacterial film as well as preparation method and application thereof
CN113186656A
Preparation method of g-C3N4 / NiS / TiO2 ternary composite photocatalytic material
CN117019195A
Formaldehyde-removing wall cloth and manufacturing method thereof
CN118181879A
